Animasi Insiden Bendera Di Hotel Yamato Menggunakan Teknologi Machinima - Achmad Fauzi; Anang Kukuh Adisusilo; Beny YV Nasution (Melek IT : Information Technology Journal, 2015)
Many historic events in Indonesia, one of the event flag incident at Yamato. Various attempts have been made so that this event still remembered by the people of Indonesia. Documentation ever made using only the media book or documentary, but at this point the book and documentary films have rarely demand by the public. This happens because of technological advances making animation that is very fast and make animation more desirable. So the need to make documentation using the latest technologies. The concept of the new technologies that will be used for the documentation of historic events that machinima. Machinima used in penlitian aims to do Reanimation (remake animation) from previous studies "Reconstruction tearing Flag Hotel Yamato Using Augnmented Reality with Marker GIS (Geographic Information System)" which will provide a new attraction, because people are now many who have forgotten This historic event. So so is appropriate if documentation of previous studies may in Reanimation using machinima technology by utilizing the Unity Game Engine to record a scene or a scene and combine all scenes recorded using machinima software technology. Based on the results of tests conducted on several correspondents showed respondents who prefer animations which have direanimasi by 79%.